Discussion of Developer Level Management Strategy in Enabler Open Platform - Zhengfeng Zhang; Xu’ang Jiang; Dan Wang (Dianxin kexue)
The related concept of open platform and developer level management strategy were introduced，the development trend of open platform was analyzed.Then the demand and current situation of developer level management strategy in telecoms operator open platform were especially discussed，and its problems were pointed out，at last some recommendations to improve the developer level management strategy in enabler open platform were given.